Multi-tissue metabolomic profiling reveals potential mechanisms of cocoon yield in silkworms (Bombyx mori) fed formula feed versus mulberry leaves - Wu, Xuehui; Chen, Xuedong; Ye, Aihong; Cao, Jinru; He, Ruimin; Pan, Meiliang; Jin, Feng; Ma, Huanyan; Zhou, Wenlin (Frontiers in Molecular Biosciences, 2022)
Use of formula feed (FF) for silkworms for all instars, has promoted transformation and progress in traditional sericulture. However, the cocoon yield of FF silkworms has failed to reach that of silkworms fed mulberry leaves (ML). The biological mechanisms underlying this phenomenon have not been well described. This study aimed to identify metabolic mechanisms and potential biomarkers relating to the poor cocoon yield of FF silkworms. In this study, silkworms received treatments of either ML (ML group) or FF (FF group) for all instars. At the 3rd day of the 5th instar, the midgut (MG), hemolymph (HL) and posterior silk gland (PSG) were collected for the metabolome profiles detection. The remaining silkworms were fed ML or FF until cocooning for investigation. The whole cocoon yield (WCY) was significantly higher in the FF group than the ML group (P < 0.05), whereas the cocoon shell weight (CSW) and cocoon shell rate (CSR) were significantly lower in the FF group (P < 0.05). A total of 845, 867 and 831 metabolites were qualified and quantified in the MG, HL and PSG of the FF silkworms, respectively. Correspondingly, 789, 833 and 730 metabolites were quantified in above three tissues of the ML group. Further, 230, 249 and 304 significantly different metabolites (SDMs) were identified in the MG, HL and PSG between the FF and ML group, respectively. Eleven metabolic pathways enriched by the SDMs were mutual among the three tissues. Among them, cysteine and methionine metabolism, arginine biosynthesis, and arginine and proline metabolism were the top three pathways with the highest impact value in the PSG. Six biomarkers were obtained through biomarker analysis and Pearson correlation calculation. Among them, homocitrulline, glycitein, valyl-threonine, propyl gallate and 3-amino-2,3-dihydrobenzoic acid were positively correlated with WCY, but negatively correlated with CSW and CSR (P < 0.05). An opposite correlation pattern was observed between 3-dimethylallyl-4-hydroxyphenylpyruvate and the three cocoon performance traits. Overall, three key metabolic pathways and six biomarkers associated with cocoon yield were interpreted, and should provide directions for formula feed optimization in factory-raised silkworms.